Reception analysis of popular feminism in the series Gadis Kretek on Netflix - Auliadinanti, Maria Adiska; Wulandari, Zhafira; Wibisono, Khairunnisa Azzahra (Universitas Padjadjaran, 2025)
Background: Feminism in popular culture is currently growing, one of which is through television or drama series. Active female advocates are increasingly creating female-centered and feminist content. The presence of feminism in popular culture makes this understanding more widely understood by the public. Gadis Kretek is one form of popular culture that can popularize feminism. Purpose: This research aims to find out how the audience interpreted the feminism issues contained in the Gadis Kretek series based on their perspectives and experiences, especially regarding the acceptance of feminism discourse, Jeng Yah as the key character of feminist heroism, and the Gadis Kretek series as the spearhead of the spread of popular feminism. Method: This descriptive qualitative research uses Stuart Hall's reception analysis of Gadis Kretek's six audiences. The data was collected using in-depth semi-structured interviews. Results: Based on the findings, all of them are in a dominant-hegemonic reading position, which agrees that Jeng Yah experienced many challenges in fighting for women's equality. This study shows that only two informants are in the dominant-hegemonic reading position when considering Jeng Yah as a key character of feminist heroism. At the same time, two are in a negotiated position, and two take an oppositional stance. The study also found that five informants were in the dominant-hegemonic position by agreeing that the series could be used to spread feminism in popular culture. In contrast, one informant disagreed and put her in the oppositional position. Conclusion: The audience of Gadis Kretek's series constructed the meaning of feminism through different perspectives and experiences. However, most informants saw Gadis Kretek as a means to spread popular feminism. Implications: This research can provide insights for feminist filmmakers in creating strong female characters and portraying the struggles and roles of women in a more accurate and empowered way in society.